1986
DOI: 10.1159/000234064
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Kurloff Cells in Guinea Pig Thymus

Abstract: One single injection of estradiol to male guinea pigs resulted in the appearance of Kurloff cells in the thymus and spleen in a maximal number after 2–3 weeks. In both organs, Kurloff cells of three categories were observed with different size and number of the inclusion(s). In the thymus, cells with small and medium-sized inclusions were present almost exclusively among low-density thymocytes. Cells with one large inclusion were initially present among low-density cells, but with time an increasing proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Counts are higher in females than in males, and increase during pregnancy and estrus. Treatment with estrogens increases KC counts in both males and females (Ledingham, 1940;Kittas et al, 1979;Sandberg and Hagelin, 1986). It also has been suggested that immunologic stimulation can raise KC counts (Revell, 1977).…”
mentioning
confidence: 99%
“…Counts are higher in females than in males, and increase during pregnancy and estrus. Treatment with estrogens increases KC counts in both males and females (Ledingham, 1940;Kittas et al, 1979;Sandberg and Hagelin, 1986). It also has been suggested that immunologic stimulation can raise KC counts (Revell, 1977).…”
mentioning
confidence: 99%
“…Neither estradiol nor serum from estrogenized animals induced the formation of Kurloff cells in vitro (SANDBERG and HAGELIN, 1986). The real function of estrogen binding sites remains unknown, although low affinity estrogen binding sites could be detected in Kurloff cell cytosol (LANDEMORE et al, 1988).…”
Section: Discussionmentioning
confidence: 99%